1979
DOI: 10.1007/bf02277575
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phosphorus on growth and iron nutrition of millet and sorghum

Abstract: At the end of twenty-four days, two plants from each treatment were supplied with 0.31 ~tci/ml of radioactive iron (5~Fe) (with the same P levels used to grow them) and then allowed to absorb the 55Fe for 3 hours after which they were harvested, separated into roots and shoots.The two components were wet-ashed separately, and assayed for 5SFe. The rest of the plants in Hoagland solution were also harvested, separately into roots and shoots. The components parts were also wet-ashed separately and assayed for ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1981
1981
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Phosphorus deficiencies are indicated at all soil sites when compared with P concentrations reported by Ajakaiye (1979). Phosphorus availability can be depressed in low pH soils by the formation of Al phosphate compounds (Birch 1951).…”
Section: Elemental Toxicities and Deficienciesmentioning
confidence: 96%
See 1 more Smart Citation
“…Phosphorus deficiencies are indicated at all soil sites when compared with P concentrations reported by Ajakaiye (1979). Phosphorus availability can be depressed in low pH soils by the formation of Al phosphate compounds (Birch 1951).…”
Section: Elemental Toxicities and Deficienciesmentioning
confidence: 96%
“…Gregory (1979) showed that N concentrations in millet fell rapidly from 60 g kg" 1 at emergence to less than 20 g kg" 1 at flowering. Ajakaiye (1979) found that maximum millet growth 24 days after planting in Hoagland's solution was achieved when millet P concentrations were between 4.9 and 5.7 g kg" 1 . Critical nutrient concentrations vary depending on the growth stage of the plant.…”
Section: Introductionmentioning
confidence: 98%
“…This link between P and Fe is in accordance with earlier studies. DeKock, Hall, and Inkson (1979) and Zheng et al (2009) have shown that elevated P supplies decrease the availability and mobility of Fe in soils as well as in plants and therewith provoke Fe deficiency-induced chlorosis (Ajakaiye, 1979).…”
Section: Natural Variation In the Mineral Element Profile Of Maize mentioning
confidence: 99%
“…Ajakaiye (1979) reported that sorghum grew best when the P concentration in its shoot (about 24 days after planting) was within the range of 2.2-8.1 g kg-I. The Phosphorus concentration was less than 2 g kg I in the shoot of plants grown without P application.…”
Section: Sorghum Mineral Compositionmentioning
confidence: 99%
“…Walker et al (1975) found sorghum more sensitive than millet to excesses of Al and Mn in plant tissues. In addition, millet seems to require less P than sorghum (Ajakaiye, 1979;Fox et aI., 1974). Millet also seems to be more tolerant than sorghum to low soil pH (Walker et aI., 1975).…”
Section: Influence Of Soil Positionsmentioning
confidence: 99%